SYNERGISTIC EFFECT OF COPPER OXIDE NANOPARTICLES FOR ENHANCING ANTIMICROBIAL ACTIVITY AGAINST K. PNEUMONIAE AND S. AUREUS - Rand M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to assess the antimicrobial activity of copper oxide nanoparticles (CuO NPs) created by method of thermal green way using basically a maize starch. Mucoid were appeared of Klebsiella pneumoniae bacterial colonies and the positive results with some biochemical tests. On the other hand, Staphylococcus aureus appeared pigmented colonies surrounded by a yellow halo because of mannitol fermentation. According to the 24 time incubation period, the CuO NPs antimicrobial activity showed of bacterial growth pathogenic K. pneumonia was 0.52 ± 0.04 cell/ml than control 1.60 ± 0.01 cell/ml .Aven as S. aureus appeared the number of bacterial growth as follow 0.79 ± 0.07 cell/ml compared with control 1.90 ± 0.01 cell/ml. The biologically effect for enhancing antimicrobial activity the percentage of resistant was decreasing from 66.6% to 22.2% when used copper oxide nanoparticles. Also, S. aureus sensitivity test showed resistant percentage was decreased from 55.5% to 33.3% at 24 hours.